Exaggerated Emphasis - McCue, Peter (Journal of Scientific Exploration, 2014)
In the Fall 2013 issue of this Journal, Jerome Clark reviewed my book Zones of Strangeness: An Examination of Paranormal and UFO Hot Spots (Journal of Scientific Exploration 27(4):735–737). I was surprised to see that so much of the review is taken up with an obsessively pedantic diatribe against my use (misuse, in Clark’s view) of exclamation marks. (Without naming the person, he also accuses another writer of the same ‘offence.’) One could argue that exclamation marks add color and nuance to writing, but Clark seems to have an almost phobic aversion to them, since he notes: “Exclamation marks in other than quoted material, including the title of a book, can be found under my byline. In each case, I was not responsible, and the marks were inserted editorially without my consent.” With respect to my book, Clark is guilty of gross exaggeration, since he writes: When one removes end notes, bibliography, and index, one is left with 490 pages of text. Barely one is deprived of an exclamation point, and many boast multiple ones, at times in succeeding sentences. From that, a reader might wrongly infer that the text contains some 490 or more exclamation marks. In fact, the book as a whole contains 173 (including exclamation marks within quotations). Peter A. McCue Bearsden, Scotland p.a.mccue@btinternet.com